Vernacular design: adaptation of traditional Malay motifs for modern ceramic ‘Lubang Angin’ design / Suraina Isahak, Verly Veto Vermol and Rusmadiah Anwar - Isahak, Suraina; Vermol, Verly Veto; Anwar, Rusmadiah (Universiti Teknologi MARA, 2018)
Traditional Lubang Angin concept on a wooden Malay houses detailed the innovation of human civilization creativity and innovation of finding design solution to a design problem in older Malay architectural houses. It prevailed the incorporation of green and sustainable technology design through detail aesthetic wood carving of craftsmanship that functioned to cools down buildings, absorbs moisture during the evaporation phase and lowers humidity in a natural way and providing a pleasant environment. These traditional cooling technologies however have been vastly imported outside Malaysia. Throughout its commercialization of business oriented, the traditional Malay motifs of lubang angin are no longer inherited into the design. This research paper discusses on the traditional iconic Malay motif that can be potentially implement for future lubang angin.